Narrative Psychiatry and Family Collaborations. - Jørring, Nina Tejs.; Alexander, June; Epston, David ([Place of publication not identified] : Routledge, 2022)
Narrative Psychiatry and Family Collaborations is about helping families with complex psychiatric problems by seeing and meeting the families and the family members, as the best versions of themselves, before we see and address the diagnoses. This book draws on 10 years of clinical research and contains stories about helping people, who are heavily burdened with psychiatric illnesses, to find ways to live a life as close as possible to their dreams. The chapters are organized according to ideas, values, and techniques. The book describes family-oriented practices, narrative collaborative practices, narrative psychiatric practices, and narrative agency practices. It also talks about wonderfulness-interviewing, mattering practices, public note taking on paper charts, therapeutic letter writing, diagnoses as externalized problems, narrative medicine, and family community meetings. Each chapter includes case studies that illustrate the theory, ethics and practice, told by Nina Jorring in collaboration with the families and colleagues. The book will be of interest to child and adolescent psychiatrists and all other mental health professionals working with children and families.
Introduction; Forword by David Epston; Part 1: From individualised to family-oriented practices; 1: A narrative family-psychiatrist; 2: Collaborative Family Therapy; Part 2: Narrative collaborative practices; 3: I am not the problem! We are the heroes!; 4: Mattering is at the heart of the matter; 5: Not untidy scribbles but a beautiful illustration of my life; 6: The helping map as a guiding light; 7: Therapeutic letter-writing; 8: Telling stories that make sense and inspire; Part 3: Narrative Psychiatric practices; 9: Naming? How might a diagnosis be best for me?; 10: Me, the Medicine and My Diagnosis; 11: Developing and co-creating shared wisdom; 12: Empowering the entire family; 13: Family Community meetings that matter; Part 4: Narrative agency practices; 14: Weaving the collaborative spirit through all our practices; 15: A continuously curious learning team; 16: The art of true helping; do dare to care; Afterword by David Epston; Addendum
Keywords: Family psychotherapy; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family